2022
DOI: 10.1021/acsptsci.2c00204
|View full text |Cite
|
Sign up to set email alerts
|

Amide-functionalized 1,2,4-Triazol-5-amines as Covalent Inhibitors of Blood Coagulation Factor XIIa and Thrombin

Abstract: To counteract thrombosis, new safe and efficient antithrombotics are required. We herein report the design, synthesis, and biological activity of a series of amide-functionalized acylated 1,2,4-triazol-5-amines as selective inhibitors of blood coagulation factor XIIa and thrombin. The introduction of an amide moiety into the main scaffold of 3-aryl aminotriazoles added certain three-dimensional properties to synthesized compounds and allowed them to reach binding sites in FXIIa and thrombin previously unaddres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…We found that no efficient synthesis toward unsymmetrical aminotriazole-based N , N ′-disubstituted formamidines 20 is known. Recently, we reported practical synthetic methods for 1,2,4-triazol-5-amines that seemed to be suitable starting materials for formamidines 20 . Thereby, we initiated the development of an efficient and universal approach allowing access to desired N , N ′-disubstituted formamidines 20.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that no efficient synthesis toward unsymmetrical aminotriazole-based N , N ′-disubstituted formamidines 20 is known. Recently, we reported practical synthetic methods for 1,2,4-triazol-5-amines that seemed to be suitable starting materials for formamidines 20 . Thereby, we initiated the development of an efficient and universal approach allowing access to desired N , N ′-disubstituted formamidines 20.…”
Section: Resultsmentioning
confidence: 99%
“…HRMS was performed with a MicrOTOF-QII (Bruker) instrument. The HPLC method to determine the purity of compounds, as well as the yields in method development procedures, is as follows: equipment 1, pump L-7100, degasser L-7614, autosampler L-7200, UV detector L-7400, interface D-7000, data transfer D-line, data acquisition HSMS software (LaChrom, Merck Hitachi); equipment 2, pump LPG-3400SD, degasser DG-1210, autosampler ACC-3000T, UV detector VWD-3400RS, interface Dionex UltiMate 3000, data acquisition Chromeleon 7 (Thermo Fisher Scientific); LiChrospher 60 RPselect B (5 μm) column, LiChroCART 250–4 mm cartridge; flow rate 1.0 mL/min; injection volume 5.0 μL; detection at λ = 210 nm; solvents A (demineralized water with 0.05% (v/v) trifluoroacetic acid) and B (acetonitrile with 0.05% (v/v) trifluoroacetic acid); gradient elution (% A), 0–4 min 90%, 4–29 min gradient from 90 to 0%, 29–31 min 0%, 31–31.5 min gradient from 0 to 90%, and 31.5–40 min 90% . The purity of compounds 21l – q was analyzed without trifluoroacetic acid addition to solvents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few potent and selective small molecule inhibitors of FXIIa are in development (Figure ). We previously reported inhibitor “ RA ” as a potent and selective inhibitor of FXIIa . In this study, we combined a small library of 32 triazole and triazole-like analogs of inhibitor RA to be evaluated for FXIIa inhibition using a chromogenic substrate hydrolysis assay under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 As this formed thrombus blocks the blood supply to important organs completely or partially, thrombosis can trigger major cardiovascular disorders, which represent leading global causes of mortality. 1,4,5 Conventionally, anticoagulants are used to prevent thrombosis. 6 As anticoagulants also prevent blood coagulation when it is desired, an increased risk for internal bleeding is a major disadvantage of an anticoagulant application.…”
Section: Introductionmentioning
confidence: 99%